2020
DOI: 10.1097/ede.0000000000001314
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Unknown

Abstract: Background: Black, Hispanic, and Indigenous persons in the United States have an increased risk of SARS-CoV-2 infection and death from COVID-19, due to persistent social inequities. However, the magnitude of the disparity is unclear because race/ethnicity information is often missing in surveillance data. Methods: We quantified the burden of SARS-CoV-2 notification, hospitalization, and case fatality rates in an urban county by racial/ethnic group using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Although this analysis was restricted to 16 jurisdictions with more complete case and race and ethnicity information, 23% of cases from these jurisdictions were missing data on race and ethnicity. Differences in data completeness by race and ethnicity could lead to underestimation of disparities (10). Restriction to 16 jurisdictions also limits the generalizability of these findings, because they are based on only 23% of the national population of persons aged <25 years; in addition, disparities could vary at geographic subdivisions within states.…”
Section: Figure Rate Ratios* Comparing Covid-19 Incidence † Among Ramentioning
confidence: 99%
“…Although this analysis was restricted to 16 jurisdictions with more complete case and race and ethnicity information, 23% of cases from these jurisdictions were missing data on race and ethnicity. Differences in data completeness by race and ethnicity could lead to underestimation of disparities (10). Restriction to 16 jurisdictions also limits the generalizability of these findings, because they are based on only 23% of the national population of persons aged <25 years; in addition, disparities could vary at geographic subdivisions within states.…”
Section: Figure Rate Ratios* Comparing Covid-19 Incidence † Among Ramentioning
confidence: 99%
“…Data gaps regarding COVID-19 cases were noted early in the pandemic, particularly a lack of data https://doi.org/10.1017/cts.2021.800 concerning what turned out to be significant disparities in community disease burden. [10][11][12] Data collected by hubs was generated by conducting interviews with partners and hosting Community Engagement Studios to learn directly from community members (Table 3). A few hubs added questions to regularly administered surveys or developed new surveys that community partners then circulated.…”
Section: Groupsmentioning
confidence: 99%
“…As of February 21, 2021 the number of the coronavirus 2019 (COVID-19) cases are over 28.1 million and COVID-19 have claimed over 498,000 lives in the United States ( the New York Times, 2021 ) Many studies have reported that racially and ethnically marginalized groups such as Black/African American and Hispanic persons are at higher risk of COVID-19 ( Adhikari et al, 2020 ; Bassett et al, 2020 ; Chen and Krieger, 2020 ; Gold et al, 2020 ; Holmes et al, 2020 ; Krieger et al, 2020 ; Labgold et al, 2021 ; Li et al, 2020 ; Muñoz-Price et al, 2020 ; Poteat et al, 2020 ; Rogers et al, 2020 ; Rossen et al, 2020 ; Selden and Berdahl, 2020 ). Structural racism at the root of differences in pre-existing conditions, access to health care and healthy food, and less favorable environment for social distancing such as living high dense area and working in essential industries (e.g., health sector, food services, transportation) may be related to disproportionate impacts of COVID-19 ( Chowkwanyun and Reed, 2020 ; Krieger, 2020 ; Laurencin and McClinton, 2020 ; Poteat et al, 2020 ; Rogers et al, 2020 ; Selden and Berdahl, 2020 ; Yancy, 2020 ).…”
Section: Introductionmentioning
confidence: 99%